Weissella cibaria riboflavin-overproducing and dextran-producing strains useful for the development of functional bread - Hernández-Alcántara, Annel M.; Chiva, Rosana; Mohedano, María Luz; Russo, Pasquale; Ruiz-Masó, José Ángel; del Solar, Gloria; Spano, Giuseppe; Tamame, Mercedes; López, Paloma (Frontiers in Nutrition, 2022)
This work describes a method for deriving riboflavin overproducing strains of Weissella cibaria by exposing three strains (BAL3C-5, BAL3C-7 and BAL3C-22) isolated from dough to increasing concentrations of roseoflavin. By this procedure, we selected one mutant overproducing strain from each parental strain (BAL3C-5 B2, BAL3C-7 B2 and BAL3C-22 B2, respectively). Quantification of dextran and riboflavin produced by the parental and mutant strains in a defined medium lacking riboflavin and polysaccharides confirmed that riboflavin was only overproduced by the mutant strains, whereas dextran production was similar in both mutant and parental strains. The molecular basis of the riboflavin overproduction by the mutants was determined by nucleotide sequencing of their rib operons, which encode the enzymes of the riboflavin biosynthetic pathway. We detected a unique mutation in each of the overproducing strains. These mutations, which map in the sensor domain (aptamer) of a regulatory element (the so-called FMN riboswitch) present in the 5’ untranslated region of the rib operon mRNA, appear to be responsible for the riboflavin-overproducing phenotype of the BAL3C-5 B2, BAL3C-7 B2 and BAL3C-22 B2 mutant strains. Furthermore, the molecular basis of dextran production by the six W. cibaria strains has been characterized by (i) the sequencing of their dsr genes encoding dextransucrases, which synthesise dextran using sucrose as substrate, and (ii) the detection of active Dsr proteins by zymograms. Finally, the parental and mutant strains were analyzed for in situ production of riboflavin and dextran during experimental bread making. The results indicate that the mutant strains were able to produce experimental wheat breads biofortified with both riboflavin and dextran and, therefore, may be useful for the manufacture of functional commercial breads.